Health education and the nursing practice to the premature newborn - Ana Luíza Paula de Aguiar Lélis; Maria de Fátima Antero Sousa Machado; Maria Vera Lúcia Moreira Leitão Cardoso (Rev Rene)
It is a descriptive-exploratory and qualitative research that aimed at analyzing the educational practices performed by the nurses, addressed to home care to premature newborns during hospitalization period in the neonatal unit of a reference hospital in Neonatology service, in Fortaleza-Ceará-Brazil, from May 2007 to March 2008. The data collection was carried out through semi-structured interview. The subjects were eight nurses that work in neonatal units and 14 mothers of premature newborns who were hospitalized in the Neonatal Units of the same hospital. The study revealed that the lack of systemization in the educational actions accomplished by the nurses interfered negatively in the mothers’ understanding regarding home care of the newborn after hospital discharge.